Zoobiquity [compact disc, unabridged] : what animals can teach us about health and the science of healing - Natterson-Horowitz, Barbara (Random House Audio : Books on Tape, 2012)
Cardiologist and psychiatrist Barbara Natterson-Horowitz and science writer Kathryn Bowers look at the remarkable correspondences between the way human beings and animals live, die, get sick, and heal in their natural settings, delving into an array of disciples: evolution, anthropology, sociology, biology, cutting-edge medicine and zoology, thus trying to provide a revelatory understanding of what animals can teach us about the human body and mind.